MAKNA TANDA PADA KUMPULAN PUISI ARUNG DIRI KARYA DJOKO SARYONO - Yusak Zainuddin (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
the purpose of this research is describe the meaning of Arung Diri poem collection by Djoko Saryono. The methode of the research is descriptive qualitative. With objective approach. The research data is from the words, phrase, or statement from those poem collection. The result of this research researt, there are three dominant meaning in the poem collection. Those are, religion or divinity, sosial critic and humanism. The religion meaning shows sufisme, the tasawuf is the wost dominant whereas. The social critic, dominate in critilizing the ruler attitude for their citizen, including the corruption which is being current social phenomena. White the humanism descriptive the purpose of why the human is created in this world. The conclution is there are variation meaning from the combination of two analysis Arung Diri poem collection. Those are, structure analysis and semiotic analysis.